2019
DOI: 10.1021/acssuschemeng.9b02845
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design of Azole-Based Deep Eutectic Solvents for Highly Efficient and Reversible Capture of Ammonia

Abstract: In this work, three azole-based ternary deep eutectic solvents (DESs) were designed for highly efficient absorption of NH3 by utilizing the weak acidity of azoles. Specifically, the DESs are composed of choline chloride (ChCl); a model azole compound such as imidazole (ImZ), triazole (TrZ), or tetrazole (TetrZ); and ethylene glycol (EG). The effects of liquid composition, pressure, and temperature on NH3 solubilities in DESs were examined systematically. It is found that ChCl + TetrZ + EG displays obvious chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
74
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 68 publications
(75 citation statements)
references
References 68 publications
1
74
0
Order By: Relevance
“…The primary cause of the dramatic shift in 1 H NMR was the chemical complexing and hydrogen bonding between NH 3 and N3─H in the imidazole ring. Such a strong interaction altered the electronic environment of N3 atoms in the imidazole ring, leading to the evolution of a corresponding peak (N3─H) in 1 H NMR . However, the peak at 3.18 ppm disappeared and shifted downfield to overlap with the weak acidity proton signals.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary cause of the dramatic shift in 1 H NMR was the chemical complexing and hydrogen bonding between NH 3 and N3─H in the imidazole ring. Such a strong interaction altered the electronic environment of N3 atoms in the imidazole ring, leading to the evolution of a corresponding peak (N3─H) in 1 H NMR . However, the peak at 3.18 ppm disappeared and shifted downfield to overlap with the weak acidity proton signals.…”
Section: Resultsmentioning
confidence: 99%
“…In order to evaluate the potential of DPILs for industrial applications of NH 3 absorption, the ILs and deep eutectic solvents (DESs) reported to absorb NH 3 were compared with this work, as shown in Table . The results indicated that the NH 3 solubility in [EtOHim][NTf 2 ] is over 30‐fold greater than that of [Emim][NTf 2 ], and four‐fold greater than that of the functionalized IL [EtOHmim][NTf 2 ], which is superior to any nonmetallic ILs reported so far.…”
Section: Resultsmentioning
confidence: 99%
“…As well known, ILs are composed primarily of one type of discrete anion and cation. In contrast, deep eutectic solvents (DESs) are eutectic mixtures that contain a variety of anionic and/or cationic species 12 . DESs are usually formed by the complexation of a quaternary ammonium salt with a metal halide salt or hydrogen bond donor (e.g., amide, polyol, carboxylic acid) 13 .…”
Section: Introductionmentioning
confidence: 99%
“…The addition of a third component to the binary DESs can affect the solubility of NH 3 . Zhong et al [ 123 ] prepared a ternary DES by combining ChCl with EG and tetrazole and compared the solubility of NH 3 of ternary DES with ChCl/EG and EG. ChCl/tetrazole/EG (3:7:14) showed greater absorption capacity compared to ChCl/EG (3:14) and EG.…”
Section: Capture Of Acidic Gasesmentioning
confidence: 99%